Markobar: Local Wisdom of the Oral Tradition of the Mandailing People - Alhidayath Parinduri; Anita Yuningsih; Nursukma Suri; Pujiati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Indonesia is a country that has a variety of cultures or often referred to as multicultural. In this research, the author is interested in discussing one of the cultures in Indonesia, namely the Markobar tradition in Mandailing tribal communities. The Mandailing tribe is one of the various ethnicities in Indonesia. The majority of the people of this tribe inhabit the Mandailing Natal Regency area, North Sumatra Province. Simply put in Mandailing language, Markobar means to speak. This shows that Markobar is the local wisdom of Mandailing tribal people in the form of oral tradition. Local wisdom is a cultural element that must be explored, studied, and revitalized because its essence is so important in strengthening the foundation of national identity in facing the challenges of globalization. The question that arises next is by looking at the rapid development of technology and science whether the Markobar tradition is able to maintain its existence in the midst of globalization.